Multimodality and Social Practices in Institutional Websites of Thai Universities - Rungruangsuparat, Benjawan (rEFLections, 2017)
Among the higher education institutes in a borderless world of academics, Thai universities have strived to introduce themselves and promote more understanding about their social practices. It has been assumed that merely the highlighted materials and distinctive landscapes were mainly communicated. Yet, the social practices were also presented in multimodal sites where global viewers could controllably investigate and arbitrarily interpret the underlying messages through given signifiers and contextual frame settings. The objective of this study was to explain how the multimodal texts were employed in presenting the social practices by the academic institutions’ websites in Thailand, one of South East Asia countries. The data collection covered the homepages, the introduction/about, news and event webpages of eight Thai university websites in four different parts of Thailand from March 16 to June 1, 2016. Two critical analysis tools, Multimodal Discourse Analysis (Kress & van Leeuwen, 2006) and Frame Analysis (Goffman, 1986), were used/adopted to analyze the practices presented in the English websites of the eight Thai universities. The findings disclosed the shared social practices in terms of academic, cultural, social life, institutional ideologies and qualification aspects that were transcended from producers to receivers by visual designs and textual communication. The institutional practices reflected not only the main tasks of educational institutes and their members, but also locally cultural factors and public relations concerns presented in an online media platform.